Olfactory Receptor Gene Regulation in Insects: Multiple Mechanisms for Singular Expression - Mika, Kaan; Benton, Richard (Frontiers in Neuroscience, 2021)
The singular expression of insect olfactory receptors in specific populations of olfactory sensory neurons is fundamental to the encoding of odors in patterns of neuronal activity in the brain. How a receptor gene is selected, from among a large repertoire in the genome, to be expressed in a particular neuron is an outstanding question. Focusing on Drosophila melanogaster, where most investigations have been performed, but incorporating recent insights from other insect species, we review the multilevel regulatory mechanisms of olfactory receptor expression. We discuss how cis-regulatory elements, trans-acting factors, chromatin modifications, and feedback pathways collaborate to activate and maintain expression of the chosen receptor (and to suppress others), highlighting similarities and differences with the mechanisms underlying singular receptor expression in mammals. We also consider the plasticity of receptor regulation in response to environmental cues and internal state over the lifetime of an individual, as well as the evolution of novel expression patterns over longer timescales. Finally, we describe the mechanisms and potential significance of examples of receptor co-expression.